Exploring a model of care for frequent callers to counselling helplines. (2nd January 2021) - Vivekananda, Kitty; Cuppari, Anita; Jenkins, Tabitha; Usatoff, Alexsandra
ABSTRACT : Objective: Very little has been articulated in the literature about strategies for managing frequent callers to helplines. This study aims to explore and clarify the current model of care for callers using helplines frequently due to their complex mental, physical and social needs. Methods: Semi-structured interviews were conducted with 10 senior clinical supervisors at four national helplines in Australia. The study took place between April and October, 2017. A thematic analysis was conducted to identify the main strategies used for the management of frequent caller cases. Results: The raw data themes emerging from the semi-structured interview transcripts were combined into four overarching main themes (i) undertaking case review; (ii) developing case coordination/management plans; (iii) staff supervision and support and (iv) outcomes of case coordination. Discussion: These results indicate that helplines use a systematic model of care for managing frequent callers that has not appeared in the previous research. Better integration between helplines and face-to-face services is required for the mental healthcare of clients with complex needs. This study provides the foundation to develop best practice guidelines for supporting frequent callers.